Low Power Consumption Substrate-Emitting DFB Quantum Cascade Lasers - Chuan-Wei Liu; Jin-Chuan Zhang; Zhi-Wei Jia; Ning Zhuo; Shen-Qiang Zhai; Li-Jun Wang; Jun-Qi Liu; Shu-Man Liu; Feng-Qi Liu; Zhan-Guo Wang (Nanoscale Research Letters, 2017)
Abstract In the present work, an ultra-low power consumption substrate-emitting distributed feedback (DFB) quantum cascade laser (QCL) was developed. The continuous-wave (CW) threshold power dissipation is reduced to 0.43 W at 25 °C by shortening the cavity length to 0.5 mm and depositing high-reflectivity (HR) coating on both facets. As far as we know, this is the recorded threshold power dissipation of QCLs in the same conditions. Single-mode emission was achieved by employing a buried second-order grating. Mode-hop free emission can be observed within a wide temperature range from 15 to 105 °C in CW mode. The divergence angles are 22.5o and 1.94o in the ridge-width direction and cavity-length direction, respectively. The maximum optical power in CW operation was 2.4 mW at 25 °C, which is sufficient to spectroscopy applications.